2021
DOI: 10.1126/sciadv.abh2340
|View full text |Cite
|
Sign up to set email alerts
|

A widely diverged locus involved in locomotor adaptation in Heliconius butterflies

Abstract: Heliconius butterflies have undergone adaptive radiation and therefore serve as an excellent system for exploring the continuum of speciation and adaptive evolution. However, there is a long-lasting paradox between their convergent mimetic wing patterns and rapid divergence in speciation. Here, we characterize a locus that consistently displays high divergence among Heliconius butterflies and acts as an introgression hotspot. We further show that this locus contains multiple genes related to locomotion and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 89 publications
1
8
1
Order By: Relevance
“…Additionally, we found that an H. erato Eastern SHDR (Fig. 4B ) overlapped with a locus recently identified to be differentiated across many pairs of subspecies in several Heliconius species and shown to affect wing beat frequency in Drosophila 74 . Thus, future studies could focus on functionally testing some of these candidates and ascertain the potentially adaptive functions of candidate regions.…”
Section: Resultssupporting
confidence: 56%
“…Additionally, we found that an H. erato Eastern SHDR (Fig. 4B ) overlapped with a locus recently identified to be differentiated across many pairs of subspecies in several Heliconius species and shown to affect wing beat frequency in Drosophila 74 . Thus, future studies could focus on functionally testing some of these candidates and ascertain the potentially adaptive functions of candidate regions.…”
Section: Resultssupporting
confidence: 56%
“…Second, within the melpomene-silvaniform clade, we obtained a robust pattern in which the common ancestor of H. besckei, H. numata and H. ismenius first split off from the rest, rendering the silvaniform species paraphyletic (Figure 2). This is contrary to a common belief that the silvaniforms are monophyletic (Heliconius Genome Consortium 2012; Kozak et al 2015;Jay et al 2021;Kozak et al 2021;Zhang et al 2021). Third, the P1 inversion on chromosome 15 involved in wing pattern mimicry likely introgressed from H. numata into H. pardalinus based on species tree topologies (Figures 2 and 3) and direct modeling of introgression (Figure S18), although where and when it originated remain uncertain.…”
Section: An Updated Phylogeny Of Heliconiusmentioning
confidence: 78%
“…All four scenarios a – d confirm paraphyly of the silvaniform species ( H. besckei, H. numata and the pardalinus-hecale clade), consistent with some recent phylogenomic studies (Zhang et al 2016; Massardo et al 2020; Cicconardi et al 2023). Monophyly of the silvaniforms was suggested in concatenation/sliding-window analysis (Heliconius Genome Consortium 2012; Kozak et al 2015; Kozak et al 2021; Zhang et al 2021), but this conclusion may suffer from a failure to account for deep coalescence (Edwards et al 2016). Our species tree search under the MSC ( Figures 1A and 2A ) accounts for incomplete lineage sorting but does not account for gene flow.…”
Section: Resultsmentioning
confidence: 99%
“…Coupled with the effects of adaptive gene sharing, diversifying and adaptive selection are expected to create a mosaic genome, with some parts of the genome having very little divergence between species, while other parts may show strong interspecific differentiation, so called genomic 'speciation islands' . Such islands were reported in several animal (Duranton et al, 2018;Irwin et al, 2018;Hejase et al, 2020;Zhang et al, 2021) and plant (Renaut et al, 2013;Tavares et al, 2018;Papadopulos et al, 2019) species, including the high-and low-elevation Senecio species on Mount Etna, where the genes with high interspecific differentiation clustered around the regions with quantitative trait loci responsible for phenotypic differences between the species (Chapman et al, 2016). However, how much adaptive gene sharing occurs in this Senecio hybrid zone remains to be tested.…”
Section: Adaptive Introgressionmentioning
confidence: 95%